Mutual coupling reduction in circularly polarized dielectric resonator MIMO antenna - J. Iqbal; U. Illahi; M. I. Sulaiman; M. Alam; MS. Mazliham; L.S Ding (Institute of Advanced Engineering and Science, 2019)
In this article a novel circularly polarized (CP) rectangular dielectric resonator antennas (RDRA’s) array has been designed. A unique conformal feeding strip has been used to excite the RDRA’s having a distance of λ/2. Various techniques are investigated to reduce mutual coupling (MC). Different formations, comprise of reorientation of the antennas have been employed to suppress MC and to enhance CP bandwidth. By the unique orientation the mutual coupling has been reduced by 14 dB. A broadband circular polarization over a bandwidth of 18.8% in conjunction with an impedance matching bandwidth of 11.3 % has been achieved. The design has been modeled and simulated using computer simulation technology (CST). Two different simulation techniques i.e. finite integration technique (FIT) and Finite element method (FEM) have been used to compute and validate the results respectively. A significant resemblance in results have been observed.